The interaction between the tennis court and the player: how does surface affect leg stiffness? - Maquirriain, J. (Sports Biomechanics, 2013)
An adequate level of leg stiffness is necessary for an optimal tennis performance and leg stiffness should be adapted to frequently changing surfaces as tennis players usually play on different courts. The aim of this study was to evaluate leg stiffness in competitive tennis players on different court surfaces. Ten healthy competitive tennis players (nine men and one woman; mean age=17.6±3.2 years) underwent leg stiffness testing by modeling the vertical ground reaction force using an optical system. Flight time and contact time were determined during hopping on two different tennis court surfaces (clay and acrylic). No significant difference was found in the flight time, contact time, and jump height between the surfaces. No significant difference in leg stiffness was found between the surfaces (18.25±5.8 and 19.27±4.9kN/m for clay and acrylic, respectively; p=0.28). This study demonstrated that contact time and flight time as well as leg stiffness of tennis players remained unchanged when hopping on two different tennis surfaces. Results of this research provide objective data regarding the tennis-specific loading of the locomotor system and proper mechanical adaptation of the player on different surfaces, which may be useful for testing protocols and planning training programs.